2017
DOI: 10.2339/politeknik.368552
|View full text |Cite
|
Sign up to set email alerts
|

AA2024 Alüminyum Alaşımına Uygulanan Yaşlandırma Yöntemlerinin İşlenebilirliğe Etkisinin Taguchi ve Anova ile Araştırılması

Abstract: AA2024 alüminyum alaşımına uygulanan yaşlandırma yöntemlerinin işlenebilirliğe etkisinin taguchi ve anova ile araştırılması Investgation of effects of the aging methods applied on AA2024 aluminum alloys on machinability with taguchi ond anova Yazar(lar) (Author(s)): Necati YALÇIN, Yunus KAYIR, Sibel ERKALBu makaleye şu şekilde atıfta bulunabilirsiniz (To cite to this article): Yalçın N., Kayır Y. ve Erkal S., "AA2024 alüminyum alaşımına uygulanan yaşlandırma yöntemlerinin işlenebilirliğe etkisinin taguchi ve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Thus, it was stated that the spindle rotates and there is a loss of information while sensing and capturing the power (spindle load) due to the damping effect of the spindle rotor caused by inertia, and chip clogging in the drill flutes may cause a change in the power data [11]. In another study, it has been suggested that the spindle load information changes randomly because the low-frequency changes in drilling torque due to chips stuck in the hole cannot be captured by the spindle load signal [1]. Due to the aforementioned conditions, the spindle load R 2 value is considered to be relatively low compared to Fz and Mz.…”
Section: Effects Of Cutting Parameters On Spindle Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was stated that the spindle rotates and there is a loss of information while sensing and capturing the power (spindle load) due to the damping effect of the spindle rotor caused by inertia, and chip clogging in the drill flutes may cause a change in the power data [11]. In another study, it has been suggested that the spindle load information changes randomly because the low-frequency changes in drilling torque due to chips stuck in the hole cannot be captured by the spindle load signal [1]. Due to the aforementioned conditions, the spindle load R 2 value is considered to be relatively low compared to Fz and Mz.…”
Section: Effects Of Cutting Parameters On Spindle Loadmentioning
confidence: 99%
“…The material AA2024-T351 is an aluminum alloy that has undergone an aging process. It is used in various industries, especially in aviation [1]. As is known, aluminum alloys have high adhesion/smearing rates.…”
Section: Introductionmentioning
confidence: 99%
“…Varyans analizi (ANOVA) girdiler ve çıktılar arasında olası ilişki şiddetinin belirlenmesinde kullanılan bir yöntemdir. Deneysel çalışmalarda sonuçların yorumlanmasında en önemli nokta deneylerde kullanılan işlem parametreleri ile deney sonrası elde edilen sonuçlar arasındaki ilişkinin belirlenmesidir [28].…”
Section: Taguchi Metodu Ve Varyans Analiziunclassified
“…Different types of electrolytes and anodizing processes are used according to the place of use of aluminum and the alloy type of aluminum used. Aluminum alloys are used in many different fields such as automotive and aerospace due to their superior properties [2,[6][7][8][9][10][11][12]. In addition to many superior properties (such as high corrosion resistance, light weight), weak tribological and interfacial mechanical properties also create some disadvantages [14].…”
Section: Introductionmentioning
confidence: 99%